FISH POPULATION AS A DYNAMIC SYSTEM WITH ELEMENTS OF SELF-REGULATION - G. A. Sudakov (Юг России: экология, развитие)
The study of fish population dynamics at system approach is most appropriate enabling consideration of processes affecting population abundance and structure and investigation of processes of stock composition and abundance regulation, fishery management. At that, it is reasonable to use some notions and ideas of the general theory of systems and cybernetics as an individual within the population and their aggregate represent compound dynamic systems studied by cybernetics.